Region of rat chromosome 8 determines complex nutrigenetic interactions under conditions of sucrose and cholesterol diets - Seda, O; Kazdová, L; Sedová, L; Liska, F; Krenová, D; Kren, V (Prague medical report, 2006)
We have previously established a congenic strain SHR-Lx that carries a differential segment of rat chromosome 8 introgressed from a model of metabolic syndrome--the polydactylous rat strain--on the genomic background of spontaneously hypertensive rat (SHR). We compared the glucose tolerance and lipid profile of adult SHR and SHR-Lx males under conditions of standard diet and diets enriched in sucrose and cholesterol, respectively. While there was no evident difference between the SHR and SHR-Lx on standard diet, the one-week sucrose administration revealed the congenic strain sensitivity to carbohydrate-induced dyslipidemia conferred by the differential segment with only mild derangement of glucose tolerance. On the other hand, the high-cholesterol diet administration for three-weeks resulted in a contrasting pattern as the congenic strain displayed significantly lower concentrations of free fatty acids and improved glucose tolerance compared to SHR. After one-month washout period, the SHR-Lx showed higher insulin, triglyceride and cholesterol concentrations together with diminished insulin sensitivity of visceral adipose tissue. In summary, we have identified a genomic region syntenic to human chromosome 11q23, which determines complex nutrigenetic interactions under conditions of sucrose- and cholesterol-enriched diets.
Keywords: Animals; konzumní sacharóza; glukózový toleranční test; lipogeneze; zvířata kongenní; Chromosomes, Plant; Blood Glucose; Glucose Tolerance Test; Lipid Metabolism; chromozomy rostlin; Insulin; Dietary Sucrose; cholesterol dietní; metabolismus lipidů; Chromosomes, Mammalian; Male; fyziologie výživy zvířat; Animals, Congenic; Animal Nutritional Physiological Phenomena; krysa rodu Rattus; potkani inbrední SHR; Lipogenesis; zvířata; mužské pohlaví; savčí chromozomy; Glycogen; inzulin; krevní glukóza; Cholesterol, Dietary; Rats; Rats, Inbred SHR; glykogen